CULTURAL APPEARANCE WITH ARCHITECTURAL LIVING ENVIRONMENT CONTEXT OF LOMBOK COMMUNITY - Kanina, Intania; Subiyantoro, Heru (Border: Jurnal Arsitektur, 2019)
Mandalika is an area with a very high tourism potential, both in terms of nature in the form of beaches and the socio-cultural community. Every year the number of tourists always increases. This tourism potential is also supported by the preservation of local culture in the local villages. This article will discuss how the culture of the people of Lombok is preserved through the realization of vernacular architecture. The research location is in the Sasak tribe settlement, namely in the village of Sade, Lombok. This study uses a descriptive method that describes the cultural manifestations of the Sasak Lombok community in the context of community treatment of the environment. Literature study is carried out to explore studies related to Sasak culture. Then the primary data collection was carried out through interviews with the local community to confirm the data from the literature study. The study results show that the realization of architecture in Sade Village is much influenced by culture in the life behavior of the Sasak people. Cultural behavior that emerges is the result of local community trust that is influenced by natural conditions, the community, and the beliefs held. Thus, the beliefs of the Sasak people influence the formation of the territorial order and building of the Sade Village community